Rosja i Rosjanie w Pamiętnikach Zygmunta Szczęsnego Felińskiego - próba rekonstrukcji stereotypu narodowego - Cybulski, Marcin (Acta Polono-Ruthenica, 2013)
The text is devoted to a problem of Russia and Russians in Zygmunt Szczęsny Feliński’s literary creativity. In wide public consciousness this writer and the Warsaw archbishop of the period of January revolt functions first of all as the author of two-volume Diaries: the monumental work representing a multi-color social panorama of the XIX century. Appearance of Russia and Russians most expressly oozes exactly in the Diaries of this author mentioned above. The article is concentrated foremost on a chart, which engulfs national onoma- stics, personal and characterologic qualities of Russians and an image of the Russian Empire as the states by turns.